(untitled) (Scientific journal of the Fergana State University, 2024)
It is known that when studying the sorption of various ions on ion exchange resins, the pH of the solution has an effect on the sorption capacity. For this reason, this article studies the dependence of solution pH on the sorption of bichromate ions to AN-31 anionite, which is used on an industrial scale. The research results show that the sorption of bichromate ions to AN-31 anion, which is used on an industrial scale, is high when the pH of the solution is acidic.